Enhancement of Dimethyl Carbonate Synthesis with In Situ Hydrolysis of 2, 2‐Dimethoxy Propane. Issue 4 (12th February 2016) - Wang, Shengping; Zhou, Jingjie; Zhao, Shuyang; Zhao, Yujun; Ma, Xinbin
Abstract: The direct synthesis of dimethyl carbonate (DMC) from CO2 and methanol is an attractive approach based on green chemistry. The influence of the addition of 2, 2‐dimethoxy propane (DMP) on DMC formation was investigated over spindle‐CeO2, cube‐CeO2, and octahedron‐CeO2 . Among these catalysts, spindle‐CeO2 showed a more favorable catalytic performance than the other CeO2 catalysts for the direct DMC synthesis with the addition of DMP. The yield of DMC was greatly improved by in situ removal of water from the reaction system through the addition of DMP. This indicated that hydrolysis of DMP overcomes the thermodynamic limitations of DMC formation and is highly effective for increasing the DMC yield. Thermodynamic calculations and the higher equilibrium constant supported this result. Abstract : Based on green chemistry, the direct synthesis of dimethyl carbonate from CO2 and cheap, renewable, and nontoxic methanol is an attractive approach. The synthesis could be significantly improved by combination with 2, 2‐dimethoxy propane hydrolysis over a spindle‐CeO2 catalyst. Thermodynamic calculations confirmed the enhanced methanol conversion into dimethyl carbonate.